Research on the effect of Cu addition on the corrosion resistance of low carbon low alloy steel - Jinliang Wang; Yujie Liu; Xiaohui Xi; Qiang Liu; Liqing Chen (Journal of Materials Research and Technology)
Cu has been regarded as an important element to improve the corrosion resistance of steels, but little was known about the role mechanism of Cu addition in low carbon low alloy steel. Therefore, on the basis of a newly-developed low carbon low alloy steel designed by the author, the effects of Cu addition on microstructure and corrosion resistance were studied in detail through microstructural characterization, accelerated corrosion test and electrochemical test. The results showed that Cu addition increased the volume fraction of retained austenite, significantly improving the compactness of corrosion film and the stability of boundaries, and thus decreasing the corrosion rate due to the inhibition of Cl− into the matrix and intergranular corrosion, respectively. Also, Cu addition promoted the formation of CuFeO2, CuO, low angle grain boundary (LAGB) and evenly distributed internal stress. Among them, CuFeO2 and CuO concentrated at the interface between inner layer and matrix improved the protectiveness of corrosion film. The LAGB and evenly distributed internal stress effectively impeded the crack of intergranular corrosion. In addition, Cu addition increased the content of Cu-rich precipitates with FCC structure, which increased the interface energy between Cu-rich precipitates and steel matrix, accordingly resulting in a higher surface Volta potential. As a consequence, the uneven distribution of potential on steel surface deteriorated the corrosion resistance. Under the combination of multi-factors, a higher corrosion resistance was achieved in Cu-bearing low carbon low alloy steel.